Cardiac Troponin Elevation Predicts Mortality in Patients Undergoing Orthotopic Liver Transplantation. (14th July 2013) - Snipelisky, David; Donovan, Sean; Levy, Michael; Satyanarayana, Raj; Shapiro, Brian
Abstract : Introduction . While patients undergoing orthotopic liver transplantation (OLT) have high cardiovascular event rates, preoperative risk stratification may not necessarily predict those susceptible patients. Troponin T (TnT) may help predict patients at risk for cardiovascular complications. Methods . Consecutive patients undergoing OLT at Mayo Clinic in Florida between 1998 and 2010 who had TnT obtained within 10 days following surgery were included. Three groups were compared based on TnT level: (1) normal (TnT≤ 0.01 ng/mL), (2) intermediate (TnT 0.02–0.11 ng/mL), and (3) elevated (TnT> 0.11 ng/mL). Overall and cardiovascular mortality was assessed. Results . Of the 78 patients included, there was no difference in age, gender, severity of liver disease, and echocardiographic findings. Patients in the normal and intermediate TnT groups had a lower overall mortality rate (14.3% and 0%, resp.) when compared with those with elevated TnT (50%;P = 0.001 ). Patients in the elevated TnT group had a cardiovascular mortality rate of 37.5% compared with 1.4% in the other groups combined (P < 0.01 ). The elevated TnT group had a much higher mortality rate when compared with those in the intermediate group (P < 0.0001 ). Conclusion . TnT may accurately help risk stratify patients in the early postoperative setting to better predict cardiovascular complications.